New Era of Pakistan’s Embrace of China: Impact on Pakistan-U.S. Relations - Iftikhar Ali; Noraiz Arshad; Roy Anthony Rogers (China Quarterly of International Strategic Studies)
This paper delves into the interdependent relationship between China and Pakistan and its implications for regional interests. It centers on China’s expanding economic clout in South Asia, primarily through its collaboration with Pakistan. Using the theoretical framework of “hedging,” the paper examines Pakistan’s strategy for balancing its connections with both China and the United States. It also explores the role of small powers in alliance politics and how China’s growing economic and military sway in Pakistan may affect Pakistan-U.S. relations. Ultimately, the paper contends that the United States can mitigate the perceived risk of a Pakistan-China partnership by considering Pakistan’s unique geopolitical position and its intricate association with India.